1999
DOI: 10.1063/1.479187
|View full text |Cite
|
Sign up to set email alerts
|

The electronic spectrum, molecular structure, and oscillatory fluorescence decay of jet-cooled germylidene (H2C=74Ge), the simplest unsaturated germylene

Abstract: The electronic spectrum of germylidene (H2C=Ge), the simplest unsaturated germylene, has been observed for the first time. Jet-cooled H2CGe and D2CGe were produced by an electric discharge through tetramethylgermane diluted in argon at the exit of a supersonic expansion. High-resolution spectra of H2C74Ge and D2C74Ge, obtained from (CH3)474Ge prepared from isotopically enriched 74Ge metal, have been rotationally analyzed to yield the following r0 structures: r0″(CGe)=1.7908(2) Å, r0″(CH)=1.1022(5) Å, θ0″(HCH)=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 19 publications
(14 reference statements)
1
29
0
Order By: Relevance
“…High-resolution (0.04 cm −1 ) spectra of 74 GeCl were recorded using an isotopically enriched 74 GeCl 4 precursor, which was cooled to −25 • C to preserve the sample. The 74 GeCl 4 was synthesized by heating 74 Ge metal (Isoflex, 99.7%) in a closed system pressurized with 20 psi of Cl 2 (Aldrich) (15). The excitation laser was an excimer pumped Lambda Physik FL3002E dye laser equipped with an angletuned intracavityétalon.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…High-resolution (0.04 cm −1 ) spectra of 74 GeCl were recorded using an isotopically enriched 74 GeCl 4 precursor, which was cooled to −25 • C to preserve the sample. The 74 GeCl 4 was synthesized by heating 74 Ge metal (Isoflex, 99.7%) in a closed system pressurized with 20 psi of Cl 2 (Aldrich) (15). The excitation laser was an excimer pumped Lambda Physik FL3002E dye laser equipped with an angletuned intracavityétalon.…”
Section: Methodsmentioning
confidence: 99%
“…Germanium monochloride was produced using the discharge jet technique described in more detail elsewhere (15). Briefly, the room temperature vapor of germanium tetrachloride (Aldrich) was seeded in 30 psi of argon and expanded through a pulsed valve (General Valve, Series 9) into a cylindrical discharge channel.…”
Section: Methodsmentioning
confidence: 99%
“…Well-known examples of molecules that exhibit anomalous fluorescence in violation of Kasha's rule include azulene and several of the thiocarbonyl compounds ͑XYC= S͒. 34 More recently, we have discovered 35,36 that H 2 C = Si and H 2 CGe also fluoresce from the B 1 B 2 excited state, with a variety of interesting photophysical properties, including single rotational level fluorescence decays that exhibit molecular quantum beats. The occurrence of anomalous emission from all these molecules is attributable to their unique energy level structure in which the second excited electronic state is far removed from the first, so that coupling between the two excited states is minimal.…”
Section: Excited State Photophysicsmentioning
confidence: 98%
“…In 1997, Clouthier et al 1 from University of Kentucky observed the first unsaturated germylene-germylidene, which is produced by striking an electric discharge in a high-pressure argon pulse using the tetramethylgermane (TMG) vapor as the precursor. They obtained its molecular structure and the ab initio predictions, 2 electronic spectrum 2 and oscillatory fluorescence decay 2 of jet-cooled germylidene (H 2 C= Ge:), and learnt the ground state 3 of H 2 C=Ge: and D 2 C =Ge:, the stimulated emission pumping (SEP) spectroscopy 4 of the first excited singlet state of germylidene. Stogner and Grev 5 have published the extensive ab initio calculations on both germylidene and the trans-bent germyne HC≡GeH isomer.…”
Section: Introductionmentioning
confidence: 99%